758 Circadian rest-activity signatures in women with major depressive disorder. (3rd May 2021) - Yang, Hui-Wen; Chellappa, Sarah; Gaba, Arlen; Cajochen, Christian; Hu, Kun
Abstract: Introduction: Patients with major depressive disorder (MDD) show disrupted circadian rhythms and sleep, including reduced daytime physical activity and poor sleep quality. However, previous findings are masked by psychotropic medication intake, co-morbid diseases and years of chronic mental illness. Here, we aim at identifying circadian motor activity patterns in unmedicated women at the onset of MDD. Methods: Twelve young unmedicated women with MDD (Mean+-SD: 24.9+-5.2y; range: 18-33y) and eight age-matched healthy women (Mean+-SD: 24.5+-3.2y; range: 20-31y) participated in our study. Activity recordings were collected using wrist-worn wearable devices (actigraphs) for ~7 days in real-life settings. Cosinor analyses were performed to assess the amplitude and phase of the 24-h rest-activity activity rhythms. Non-parametric analyses were used to quantify interdaily stability and intradaily variability of the rest-activity rhythm. Furthermore, we calculated the mean activity level and scaling exponent alpha, which quantifies the temporal correlation in activity fluctuations, per 3-h bins across the 24-h sleep-wake cycle. Results: Women with MDD showed a significantly higher amplitude of the 24-h rest-activity activity rhythm (Mean+-SD: 332.7+-120.8 arbitrary units) than the controls (179.7+-122.9; p=0.002), elicited by higher activity levels during the daytime (0-12h after habitual wake-up time; p<0.01). In contrast, women with MDD showed a trend for lower interdaily stability levels than controls (respectively, 0.41+-0.07 and 0.46+-0.08; p=0.05). Interestingly, a significant interaction effect of "group" and "time since habitual wake" was elicited for scaling exponent alpha (p<0.001). Accordingly, women with MDD had higher alpha values during habitual sleep (0–6 hours before habitual wake-up time) than controls (respectively, 1.18+-0.22 and 1.12+-0.22). Conclusion: Unmedicated women at the onset of MDD had altered circadian motor activity patterns, as indexed by higher amplitude particularly during daytime while awake, less stable 24-h activity rhythms, and highly correlated activity patterns during sleep that closely resemble those typically occurring during wakefulness. These findings suggest that MDD per se may be associated with impaired rest-activity profiles. Ultimately, the use of wearable devices might hold important prospects for the early detection of individuals at risk for mood disorders. Support (if any): Swiss National Science Foundation Grants START #3100–055385.98, 3130-0544991.98 and 320000-108108; NIH RF1AG064312, RF1AG059867